The vitamin D receptor gene is associated with Alzheimer's disease - Lehmann, D; Refsum, H; Warden, DR; Medway, C; Wilcock, G; Smith, A (2011)
Vitamin D may have a role in brain function. Low levels have been frequently associated with cognitive decline and may contribute to diseases of the nervous system. The vitamin D receptor (VDR) is widely expressed in human brain. Vitamin D appears to be neuroprotective and may regulate inflammation in the brain. We examined two VDR polymorphisms, Apa1 and Taq1. We used DNA from 255 Alzheimer's disease (AD) cases and 260 cognitively screened elderly controls from the longitudinal cohort of the Oxford Project to Investigate Memory and Ageing (OPTIMA). The presence of each of the linked alleles, Apa1 T and Taq1 G, was associated with the risk of AD, particularly in people <75 years old: odds ratios ≥3.0 and p≤. 0.005. We also found preliminary evidence of interactions associated with AD between these polymorphisms and two other genes involved in the regulation of inflammation, interleukin-10 (IL10) and dopamine β-hydroxylase (DBH): synergy factors ≥3.4, uncorrected p<. 0.05. These associations are biologically plausible and are consistent with a role for vitamin D in AD. Nevertheless, we consider this to be a hypothesis-generating study, which needs to be replicated in a larger dataset. © 2011 Elsevier Ireland Ltd.